1994
DOI: 10.1111/j.1365-3059.1994.tb00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds for control of Septoria spp. in winter wheat based on precipitation and growth stage

Abstract: A simple forecasting model for Septoria spp. in winter wheat was developed based on historical data (1980–89) including precipitation, growth stage, disease severity and yield response to fungicide treatments. The number of days with precipitation ≥ 1 mm, calculated during a 30‐day period starting at the beginning of stem elongation (GS 32), correlated well with attacks of Septoria spp. later in the season and with the yield response in trials with fungicide treatments. Seven or 8 days with rainfall ≥ 1 mm was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 11 publications
(11 reference statements)
0
19
0
1
Order By: Relevance
“…Hansen et al (1994) encontraron una buena correlación entre la severidad de S. tritici y la frecuencia de días con más de 1 mm de lluvia durante 1 mes, comenzando en el estado fenológico de encañazón. En Argentina, Moschini (2007) halló una fuerte correlación entre la frecuencia de días con precipitaciones mayores a 7 mm y el coeficiente de infección de S. tritici, confirmando que a partir de dicho umbral (7 mm), es probable contar con la energía gravitacional y el mojado adecuados para la remoción y dispersión de las esporas de Septoria.…”
Section: Discussionunclassified
“…Hansen et al (1994) encontraron una buena correlación entre la severidad de S. tritici y la frecuencia de días con más de 1 mm de lluvia durante 1 mes, comenzando en el estado fenológico de encañazón. En Argentina, Moschini (2007) halló una fuerte correlación entre la frecuencia de días con precipitaciones mayores a 7 mm y el coeficiente de infección de S. tritici, confirmando que a partir de dicho umbral (7 mm), es probable contar con la energía gravitacional y el mojado adecuados para la remoción y dispersión de las esporas de Septoria.…”
Section: Discussionunclassified
“…Heavy rainfall during this period may cause lodging, which will reduce harvested yield (Easson et al 1993). It is, however, more likely that the negative effect of precipitation in July on yields are caused by Septoria disease, which is favoured by wet conditions during this period (Hansen et al 1994). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is because they assume, tacitly or by implication, that the main risk of infection to the upper leaf layers comes from inoculum that developed on leaves during winter and spring, before stem extension (e.g. Anonymous, 1986;Hansen et al, 1994). Previously, Bahat et al (1980) reported a ladder effect of disease progression that was affected by the distances between consecutive leaves.…”
Section: Discussionmentioning
confidence: 99%